High temperature QDs organization and re-crystallization in glass supported MgO QDs doped PMMA film - Satya Pal Singh; Archana Kumari Singh; Suraj Vishwakarma (Scientific Reports)
Abstract We have blended MgO QDs with poly (methylmethacrylate) (PMMA) thin films using solution-casting method. MgO QDs were doped at 5 wt %, 10 wt %, and 15 wt % in PMMA film and annealed for 02, 04, 06, 08, 10, 12, 14, 20, 24, and 28 h at 130 degree Celsius. We have comprehensively investigated the molecular-scale restructuring and morphological evolution of the composite films and have accounted for the reasons based on the observations made on chemical bonding, crystallinity, bandgap, Urbach energy, and fluorescence and Raman spectra. We observe that the film loses its overall crystallinity in the initial stages of annealing, which improves slightly owing to the temperature-induced limited diffusion of MgO QDs (sizes in the range of 7.0603–9.5647 nm). MgO QDs undergo coarsening at temperatures as low as 130 0C. The limited diffusion of MgO QDs allows for the formation of larger clusters, which in turn affects the local crystallinity of the composite films. We report local-scale re-crystallization driven by dispersion forces acting globally. As far as the quantum nature of forces is concerned, this work clearly demonstrates some unique energy dissipation mechanism of charge carriers in QDs via overlapping with long-range dispersion forces. The morphological evolution of the films is the outcome of the reconciliation of forces. We discuss the role of competing forces. The evolution of nano-micro scale structures inside films is governed by the reconciliation between inter- and intra-molecular forces. The temperature of the film plays an important role in facilitating the entire process. To obtain molecular-scale insights, we have estimated the crystallinity, bandgap, and Urbach energy of the pure and hybrid films. MgO QDs diffuse locally and coalesced to form larger spherical clusters. The anchoring of MgO QDs on the PMMA surface and vice-versa appears to provide thermal stability and mechanical strength to the nanocomposite films, as the MgO QDS-doped PMMA film form nanometer-sized particulates of PMMA. In contrast, the overall crystallinity of the hybrid film drastically decreases as the formation of boundaries, interfaces, and voids overwhelmed the entire process. The formation of larger nanoaggregates at later stages of annealing slightly improves the crystallinity of the films. The estimation of the bandgap and Urbach energy calculations confirm the same. The micro-level phenomenological understanding of the diffusion process of nanodots in a nearly solid film is technically important for ensuring the sustainability of such nanocomposites that undergo a heating process.